Combining three grain mutants for improved‐quality sweet corn. Issue 1 (18th March 2020) - Jompuk, Choosak; Jitlaka, Chadamas; Jompuk, Peeranuch; Stamp, Peter
Abstract: Our goal was to improve sweet corn ( Zea mays L.) by the novel approach of combining three grain mutants in one plant, shrunken‐2 ( sh2sh2 ), purple ( Pr1Pr1C1C1 ), and  opaque‐2  ( o2o2 ), for increased sugar, anthocyanin, and tryptophan content, respectively. We crossed purple  opaque‐2  waxy maize with sweet corn inbred lines. In the segregating selfed progenies, the  opaque‐2  gene was detected by the genetic marker  phi057,  the two other genes by the visual markers purple and shrunken. The purple  opaque‐2  sweet corn performed well in field tests; it had high total sugar content as required for sweet corn, improved protein quality indicated by 30% higher tryptophan content, and a 10‐fold higher anthocyanin content than yellow kernel maize. This new sweet corn germplasm is a first step toward developing specialty maize with increased health benefits.